PENGARUH STRUKTUR KEPEMILIKAN DAN GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO: THE EFFECT OF OWNERSHIP STRUCTURE AND GOOD CORPORATE GOVERNANCE ON RISK MANAGEMENT DISCLOSURE - Dinata, Marco; Yusralaini, Yusralaini; Susilatri, Susilatri (Universitas Riau, 2023)
This study aims to determine the effect of the variables of management ownership, foreign ownership, public ownership, independent commissioners, audit committees, and risk management committees on risk management disclosures. The population in this study is all manufacturing companies listed in the IDX period 2016-2021. The selection of sample in this study used the purposive sampling method. The samples selected in this study are 71 companies based on predetermined criteria. The results showed that the risk management committee had a positive and significant effect on risk management disclosure. Meanwhile, management ownership, foreign ownership, public ownership, independent commissioners and audit committees have no significant effect on risk management disclosure